Enhancing performance factor analysis through skill profile and item similarity integration via an attention mechanism of artificial intelligence - Mehrabi, Amirreza; Morphew, Jason W.; Quezada, Breejha S. (Frontiers in Education, 2024)
IntroductionFrequent formative assessment is essential for accurately evaluating student learning, enhancing engagement, and providing personalized feedback. In STEM education, understanding the relationship between skills that students have internalized (mastered) and those they are developing (emergent) is crucial. Traditional models, including item response and cognitive diagnosis models, primarily focus on emergent skills, often overlooking internalized skills. Moreover, new tools like large language models lack a complete approach for tracking knowledge and capturing complex skill relationships.MethodsThis study incorporates artificial intelligence, specifically attention mechanisms, into educational assessment to evaluate both emergent and internalized skills. We propose a modified version of Performance Factor Analysis (PFA), which assesses student abilities by analyzing past responses and comparing them with peer performance on the same items, using parameters from a sigmoid function. This model leverages attention mechanisms to capture item order-based similarity and decay principles, providing a nuanced view of student skill profiles.ResultsThe Modified Performance Factor Analysis model significantly improved discriminative power, accuracy, precision, recall, and F1 scores across various skill areas compared to traditional PFA models.DiscussionThese results indicate that the Modified Performance Factor Analysis model allows for a more accurate and comprehensive evaluation of student performance, effectively identifying both emergent and internalized skills. By integrating AI into assessment, educators gain deeper insights, enabling them to refine teaching strategies and better support students' mastery of both types of skills.